Mobile App-Enhanced Project-Based Blended Learning to Develop Consistent Study Habits in Health Sciences Education - Sudo, Hisaya; Noborimoto, Yoko; Takahashi, Jun (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study investigates the impacts of project-based blended learning (PBBL) integrated with a mobile learning app on students’ study habits in Japanese physical therapy education. The PBBL model emphasizes predominantly asynchronous learning via the mobile app supplemented strategically by synchronous sessions for interaction and motivation, and is designed to foster consistent study habits. The research employs a mixed-methods approach, analyzing quantitative data from learning logs and qualitative insights from student reflection sheets. Results demonstrate that PBBL significantly increased students’ self-study time via the mobile app, with a positive correlation between consistent study habits and academic test scores. Qualitative analysis revealed that students participating in PBBL naturally gained insights into aspects of the universal behavior model through repeated practice and reflection while working on projects as a team. Integration of the mobile app provided real-time feedback through learning logs, thereby facilitating data-driven reflection and behavioral change. This PBBL model plays a crucial role, especially for first-year students, who are often prone to academic maladjustment, by fostering the skills necessary to establish a foundation for an enriched learning experience throughout their four-year undergraduate program.